Pengembangan Modul Pembelajaran IPA Berbasis Learning Cycle 5E pada Materi Zat Aditif dalam Makanan - Nurfajriani Nurfajriani; Dyah Tri Renartika (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This study aims to (1) develop learning modules IPA-based learning cycle 5E in material additives in food based on established standards, (2) Determine the feasibility of learning modules IPA-based learning cycle 5E in material additives in food that are developed, and (3) find out the response of students towards science learning modules 5E learning cycle based on the material additives in food. This study is a research and development (Research and Development / R&D), conducted in SMP Smart Pure-Jam'iyatul MTsAl Washliyah Tembung. The instrument used was a questionnaire assessing the feasibility of modules based BSNP, questionnaire component 5E learning cycle in science learning modules, and questionnaire responses of students to the module design. Module learning science developed using learning strategies learning cycle 5E which consists of five stages: (1) the generation of interest (engagement), (2) exploration (exploration), (3) an explanation (explantion), (4) the elaboration (elaboration), and (5) evaluation (evaluation). The results showed that the modules developed fit for use according BSNP because it has been validated and obtained an average score of 3.55 contents feasibility, feasibility languages 3.63, 3.60 presentation feasibility and feasibility kegrafikaan 3.72. While the students' response to science learning modules 5E learning cycle based on the material in the food additives that have been developed to get a score of 3.54.Keywords: develop modules IPA, learning cycle 5E, material additives in food